(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article discusses the problems and prospects of the development of organic agriculture in Kyrgyzstan in the conditions of the EAEU (Eurasian Economic Union). The main focus is on the issues of insufficient awareness of the benefits of organic products, the lack of financial instruments and government support, as well as the inconsistency of national standards with international requirements. The challenges associated with the development of an effective legislative framework, improving infrastructure and overcoming information barriers are analyzed. Recommendations are also proposed for the implementation of integrated solutions to increase the competitiveness of organic agriculture, including the creation of a single digital platform to strengthen and sustainably grow the agricultural sector’s position in international markets.